A linear complexity phasing method for thousands of genomes - Delaneau, O; Marchini, J; Zagury, J (2012)
Human-disease etiology can be better understood with phase information about diploid sequences. We present a method for estimating haplotypes, using genotype data from unrelated samples or small nuclear families, that leads to improved accuracy and speed compared to several widely used methods. The method, segmented haplotype estimation and imputation tool (SHAPEIT), scales linearly with the number of haplotypes used in each iteration and can be run efficiently on whole chromosomes. © 2012 Nature America, Inc. All rights reserved.